РARTICULAR QUALITIES OF THE RENAL OSMOREGULATORY FUNCTION IN PATIENTS WITH TYPE 2 DIABETES - Kuznetsova, E.S.; Kuznetsova, A.S.; Shuhtin, V.V.; Gozhenko, A.I. (Ukrainian Journal of Nephrology and Dialysis, 2015)
The aim of the study was to examine the osmoregulatory state of renal function in patients with type 2 diabetes in a water - salt load with 0,5% NaCl in the amount of 0.5% of body weight. Materials and methods. The study involved 56patients with insulin - dependent diabetic nephropathy,24 men (42.9%) and 32 women (57.1%), aged from 38 to 81 years. The osmolality was measured by freezing point depression on osmomat 030 - D (USA). Glomerular filtration rate (GFR) was calculated by the formula GFR - EPI with subsequent determination of renal functional reserve. Results. It demonstrated that renal osmoregulatory function provides effective regulation of osmotic homeostasis even in a reduced amount of nephrons, but as the glomerular filtration rate decreses to 30 ml/min, the excretion of osmotically active substances gradually decrease too. Conclusion. Osmoregulatory disturbances in the renal function in patients with 2 types diabetes depend both on the reduction in GFR, - and on changes in the functional capacity of nephron’s tubules.